The Role of Gratitude and Big Five Personality in Shaping Quality of Life - Kumar, Dhrub; Bharti, Aprajita (Journal of Neonatal Surgery, 2025)
Quality of life (QoL) is a multidimensional construct. It is influenced by psychological, social, and environmental factors. Among psychological factors, gratitude and personality traits have been identified as important contributors to quality of life. The present study aimed to examine the relationship among quality of life, gratitude and the Big Five personality traits. Further, to explore the relationship between gratitude and the Big Five personality traits as predictors of QoL in adolescents. The study was conducted on 710 high school students (346 males and 364 females) from Classes X–XII. Participants completed the WHOQOL-BREF, the Gratitude Questionnaire (GQ-6), and the Big Five Inventory-10 (BFI-10). Pearson correlation and multiple regression analyses were applied to examine associations and predictors of quality of life. A significant positive correlation was found between gratitude and all domains of quality of life, including physical, psychological, social, environmental, and overall QoL (r = .283–.399, p < .01). Conscientiousness was positively associated with all QoL dimensions, whereas neuroticism and extraversion emerged with significant negative relationships with several domains. Regression analyses revealed gratitude as the strongest and most consistent predictor of quality of life, explaining up to 19.3% of the variance in overall QoL. Conscientiousness contributed positively to psychological, social, environmental, and overall QoL, while neuroticism and extraversion negatively predicted selected QoL dimensions. The findings highlight gratitude as a powerful psychological resource that enhances adolescents’ quality of life across multiple domains. While personality traits, particularly conscientiousness and neuroticism, also influence well-being, gratitude emerged as the most robust predictor. The study suggests that gratitude-based interventions may be effective in promoting adolescents’ psychological well-being and improving their overall quality of life.